A geomorphological approach for enhancing environmental management and conservation of landforms as protected nature objects in the Upper Daugava spillway valley (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper describes the application of geomorphological approach for environmental management and conservation of landforms. Specifically, we discuss the contribution of geomorphological field survey and adapted matrix methodology (in combination with understanding of geology) to identification, study and evaluation of those abiotic nature elements which represent geological and geomorphological heritage. We describe a case study carried out in that part of the protected landscape area “Augšdaugava” which encompasses the Upper Daugava spillway valley. The study programme reported in this paper was realized to perform inventory of landforms and geological features for recognition of objects of particular interest in terms of including them in the list of protected nature monuments. After the field reconnaissance and survey of such objects in situ, the assessment based on several criteria like scientific, aesthetic and paleogeographic value, type, rareness, integrity and representativeness was performed. Obtained data is sufficient to make a well-founded selection of the abiotic nature elements and components of geodiversity, including geological and geomorphological features, e.g. particular landforms as protected nature objects, and to substantiate the need for their conservation. Hence, the output of performed study can be used for enhancing environmental management and conservation of nature diversity and values in this region.